(-9+4i)(6-3i)=

Simple and best practice solution for (-9+4i)(6-3i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-9+4i)(6-3i)= equation:


Simplifying
(-9 + 4i)(6 + -3i) = 0

Multiply (-9 + 4i) * (6 + -3i)
(-9(6 + -3i) + 4i * (6 + -3i)) = 0
((6 * -9 + -3i * -9) + 4i * (6 + -3i)) = 0
((-54 + 27i) + 4i * (6 + -3i)) = 0
(-54 + 27i + (6 * 4i + -3i * 4i)) = 0
(-54 + 27i + (24i + -12i2)) = 0

Combine like terms: 27i + 24i = 51i
(-54 + 51i + -12i2) = 0

Solving
-54 + 51i + -12i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '3'.
3(-18 + 17i + -4i2) = 0

Factor a trinomial.
3((-9 + 4i)(2 + -1i)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-9 + 4i)' equal to zero and attempt to solve: Simplifying -9 + 4i = 0 Solving -9 + 4i = 0 Move all terms containing i to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4i = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 4i = 0 + 9 4i = 0 + 9 Combine like terms: 0 + 9 = 9 4i = 9 Divide each side by '4'. i = 2.25 Simplifying i = 2.25

Subproblem 2

Set the factor '(2 + -1i)' equal to zero and attempt to solve: Simplifying 2 + -1i = 0 Solving 2 + -1i = 0 Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1i = 0 + -2 -1i = 0 + -2 Combine like terms: 0 + -2 = -2 -1i = -2 Divide each side by '-1'. i = 2 Simplifying i = 2

Solution

i = {2.25, 2}

See similar equations:

| 6p+6-3=5p-4 | | x*100=310000*112,8 | | 3k+4=7k-12 | | 2.3x+4.98=3x+2.6 | | x*100=290600*110,1 | | x-.2x=70000 | | [10x-5]=25 | | 10f+0.80=11.70 | | P=2x+2w | | [6+3a]=15 | | x(x)+24x= | | x-.2x=50000 | | -6+5=-x | | 3y-9=9-15y | | -3p+3p=0 | | 5(2x-8)+4x= | | -10k-4=3-9k | | 2(x+8)=3(x-7) | | z^4+36=0 | | 3(x+8)+4x= | | 5h=5h+7 | | 8y-5=(-y)+2 | | -2-3y+4=6-3y | | 66y=5(13y+54) | | .10x+.70(100)=.30(100+x) | | 8b=-6+6b | | 6p(2p-3q)= | | -7-9s=-s-7-8s | | 8w-17w=-72 | | -(3x+2)-(x-1)=-(2x-2)-(2x+4) | | (2x+2)-1=-x-(x+3) | | 19-46=3(x-4)-3 |

Equations solver categories